2018
DOI: 10.1038/s41598-018-33362-6
|View full text |Cite
|
Sign up to set email alerts
|

Application of spin-crossover water soluble nanoparticles for use as MRI contrast agents

Abstract: Water soluble spin-crossover (SCO) iron(II) nanoparticles (NPs) were synthesized by the polyethylene glycol (PEG) coating of [Fe(Htrz)3-3×(NH2trz)3×](BF4)2 (x = 0, 0.1, 0.5 and 1). The NPs with x = 0.1 show gradual SCO behavior over 280–330 K in water. The relaxation times, T1 and T2, were determined and the thermally-responsive T2 values making these NPs a candidate for use as a MRI contrast agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 19 publications
3
24
0
Order By: Relevance
“…The observed variations in T 1 and T 2 between field strengths may in part be related to differences in temperature between measurements. The relaxation time temperature coefficients for deionized water were previously measured to be 0.06 s/°C (T 1 ) and 0.01 s/°C (T 2 ), respectively …”
Section: Discussionmentioning
confidence: 99%
“…The observed variations in T 1 and T 2 between field strengths may in part be related to differences in temperature between measurements. The relaxation time temperature coefficients for deionized water were previously measured to be 0.06 s/°C (T 1 ) and 0.01 s/°C (T 2 ), respectively …”
Section: Discussionmentioning
confidence: 99%
“…Average deviation from the target relaxation times was 98 ms (7.2%) and 112 ms (8.1%) for T 1 , and −4.4 ms (−5.0%) and 2.7 ms (5.4%) for T 2 at 3 and 7 Tesla, respectively. It must be noted that due to changes in the heating systems in both scanner rooms, the temperature at the time of measurement was about 1°C higher compared to the measurements for the model, leading to expected increases in T 1 14,41 …”
Section: Resultsmentioning
confidence: 90%
“…It is well known that the T1 value varies with temperature . Therefore, by constructing a system that can be adjusted so that the phantom temperature can be maintained at a level a researcher desires, it is possible to develop a phantom that has a similar T1 value as that of in‐vivo CSF.…”
Section: Discussionmentioning
confidence: 99%
“…This is probably because the T1 value changes due to the fact that the postmortem temperature is lower than the biological temperature. Tsukiashi et al measured the T1 value against the water temperature and reported the change in the temperature and in the T1 value . From this, it is certain that the T1 value largely fluctuates due to changes in temperature.…”
Section: Introductionmentioning
confidence: 99%